Ift88 regulates enamel formation via involving Shh signaling. (1st March 2022) - Kudo, Takehisa; Kawasaki, Maiko; Kawasaki, Katsushige; Meguro, Fumiya; Nihara, Jun; Honda, Izumi; Kitamura, Madoka; Fujita, Akira; Osawa, Kazuaki; Ichikawa, Kaya; Nagai, Takahiro; Ishida, Yoko; et al.
Abstract: Objectives: The ciliopathies are a wide spectrum of human diseases, which are caused by perturbations in the function of primary cilia. Tooth enamel anomalies are often seen in ciliopathy patients; however, the role of primary cilia in enamel formation remains unclear. Materials and Methods: We examined mice with epithelial conditional deletion of the ciliary protein, Ift88, ( Ift88 fl / fl ; K14Cre ). Results: Ift88 fl / fl ; K14Cre mice showed premature abrasion in molars. A pattern of enamel rods which is determined at secretory stage, was disorganized in Ift88  mutant molars. Many amelogenesis‐related molecules expressing at the secretory stage, including amelogenin and ameloblastin, enamelin, showed significant downregulation in Ift88  mutant molar tooth germs. Shh signaling is essential for amelogenesis, which was found to be downregulated in Ift88  mutant molar at the secretory stage. Application of Shh signaling agonist at the secretory stage partially rescued enamel anomalies in Ift88  mutant mice. Conclusion: Findings in the present study indicate that the function of the primary cilia via Ift88 is critical for the secretory stage of amelogenesis through involving Shh signaling.